Oxygen isotopes of seawater and oxygen and nitrogen isotopes of dissolved nitrate measured in the Gulf of Maine in October, 2016 - Nina M Whitney; Alan D Wanamaker; Megan E Switzer; Neal R Pettigrew (PANGAEA, 2021)
This dataset contains salinity and stable isotope measurements taken of water samples collected during an October 2016 research cruise in the Gulf of Maine aboard the NOAA ship Pisces. Water samples were collected at 44 different stations throughout the Gulf of Maine at various depths from the surface to the seafloor using a carousel sampler with 12 different Niskin bottles and attached to a SeaBIRD 911 CTD. Salinity was measured in situ using the SeaBird 911 CTD with auxiliary sensors. Water samples were collected from depth in Niskin bottles and transferred to triple rinsed Thermo Scientific Nalgene 4 Oz natural hdpe plastic wide mouth leakproof bottles. Parafilm was secured around the cap of each bottle to help prevent evaporation. Samples designated for δ18O(water) analyses were stored in containers in the wet lab of the boat. Samples designated for δ15N(NO3-) and δ18O(NO3-) analyses were immediately placed in a walk-in freezer set at - 8°C. Once back at port, samples were overnight shipped to the Stable Isotope Lab at Iowa State University. Frozen samples were shipped in coolers with additional ice added and, upon arrival, immediately placed back in a freezer. This dataset also contains two freshwater samples collected from the Kennebec River in November and December 2016. Samples were hand collected and stored in Thermo Scientific Nalgene 4 Oz natural hdpe plastic wide mouth leakproof bottles. Samples were shipped on dry ice to Iowa State University and processed in the same way as the other saltwater samples as detailed below. Once at Iowa State University, samples designated for δ18O(water) were stored in the temperature controlled laboratory and then analyzed using a Picarro L2130-I Isotopic Liquid Water Analyzer with attached autosampler. Three different isotopic reference standards, VSMOW, USGS 48, and USGS 47, were used. At least one reference standard sample was used per 5 samples. The average combined uncertainty (analytical and average correction factor) was ±0.20 extperthousand (2σ). Samples designated for isotopic analyses (δ15N and δ18O) of dissolved NO3- were first unfrozen at Iowa State University and filtered using 0.2 μm pore filters (Sartorius Minisart high flow syringe sterile PES membrane). Subsequently, water samples were treated with sulfamic acid (ACS grade, 99.3-100.3%) to remove any NO2- following the procedures outlined in Granger and Sigman (2009; doi:10.1002/rcm.4307). Briefly, glassware was acid washed and baked at 500°C. 60 ml of sample were treated with 600 μL 0.4M sulfamic acid (made using 10% v/v HCl) to reduce the pH to between 1.6 and 1.8, which is necessary to reduce NO2- to N2 and therefore remove it from the sample. After the reaction was allowed to occur for at least 5 min, samples were neutralized by adding 2M NaOH to the sample to return the sample to a pH of 7 (±0.5). Approximately 310 μL of NaOH were added to each sample but the exact amount of NaOH varied by sample and was determined using a pH meter. Samples were then refrozen, put on dry ice and shipped overnight to the University of California Davis Stable Isotope Facility. Samples were analyzed for δ15N(NO3-) and δ18O(NO3-) using the bacterial denitrification assay method as outlined by Sigman et al., (2001; doi:10.1021/ac010088e) and Casciotti et al., (2002; doi:10.1021/ac020113w), respectively. Isotopes were measured using a Thermoscientific Delta V Plus isotope ratio mass spectrometer coupled to a ThermoFinnigan GasBench + PreCon trace gas concentration system. Seven different reference standards were used to correct samples and report values on the international scale, Air: USGS34 KNO3, USGS35 NaNO3, Acros KNO3, Fisher KNO3, Strem KNO3, New Acros KNO3, and IAEA-NO-3 KNO3 (not used on all samples). Average analytical uncertainty (2σ) was ±0.5 extperthousand for δ15N(NO3-) and ±0.3 extperthousand for δ18O(NO3-). In order to assess the extent to which nitrification is occurring in the Gulf of Maine, we used the following equation for Δ(15, 18), first proposed by Sigman et al., (2005; doi:10.1029/2005GB002458): Δ(15, 18) = (δ15N(NO3-) - δ15Nm)-(15ε/18ε)x(δ18O(NO3-)-δ18Om) δ15Nm and δ18Om are mean δ15N and δ18O of dissolved NO3- in deep source waters, respectively. In this case, we use average values for samples taken at and below 100 m, where δ15N(NO3-) and δ18O(NO3-) remain relatively constant with depth. 15ε/18ε is the ratio of isotope fractionation factors for nitrogen and oxygen, respectively, for assimilation, which is taken to be 1 here. The propagated ([a2+b2]1/2) uncertainty for Δ(15, 18), calculated using the uncertainty associated with δ15N(NO3-) and δ18O(NO3-), is ±0.6 extperthousand (2σ).